“Rendimiento y tamaño de grano de una variedad y cinco lineas de mani (arachis hypogaea) en suelo entisol en el fundo “oasis” -Morales” - Cubas Silva, Rosa Iris (2003)
We observe the importance of the peanut and existing deficit information on the size of the grain in the yield of the variety and lines that exist in San Martin, since is the first investigation work, this one carries out with the objective of evaluating the yield and grain size and cost benefit of a variety and five peanut lines. The present work was carried out in the 1 am founded "Oasis"-Moral, in the County and Department of San Martín, in the second campaign of the year 2001, it was carried out completely with the design of Blocks randomizado with factorial arrangement and tour repetitions. Bigger production was obtained in the first place with the lines the line angelito grain boy, with 1091,70 Kg/ha, Bolisho big grain with 1041,70 Kg/ha and lastly Angelito small grain with 1000,00 Kg/ha, also with an a net value of the production the same respective lines (2118,85; 1992,30; and 1740,74).